DEVELOPMENT OF A SYSTEM MODEL OF TECHNICAL OPERATION MANAGEMENT IN TRANSPORT INFRASTRUCTURE PROJECTS (Transport systems and technologies, 2021)
The article considers the problems of quality management of repair and operation of technical means in projects of development and maintenance of transport infrastructure, which is the most important factor in improving living standards, economic, social and environmental safety. The project quality management system and planning methodology are considered. It is investigated that in order to improve this system it is necessary to solve the problem of integration of quality management principles and their adaptation to transport infrastructure projects on quality management of repair and operation of technical means and the ways of solution are shown.A set of interrelated organizational and technological tasks and measures aimed at restoring the normative transport and operational indicators of repair and operation of technical means of transport is considered.It is investigated that the process of project quality assurance at the level of quality management in transport infrastructure projects consists of the adoption of planned systematic measures to ensure the implementation of all envisaged processes. On the basis of researches the system model of criteria by means of which it is possible to define system efficiency of development and realization of the corresponding projects of transport infrastructure is offered.As a result of solving this problem, a model of management and decision support for diagnostics of technical means in transport infrastructure projects has been developed, which opens prospects for planning and timely maintenance and repair of technical means of transport to ensure and improve traffic safety.
Keywords: technical means, model, control system, monitoring, project, quality, system analysis.